Survei Minat Olahraga Bola Voli Siswa MA Al Ijtihad Danger Kabupaten Lombok Timur Tahun 2023 - Primayanti, Intan (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2023)
Someone carrying out activities, activities, or behavior is always based on interest, which in this study was especially in the sport of volleyball. This study aims to determine interest in volleyball at MA Al Ijtihad Danger, East Lombok Regency in 2023. This research is a descriptive study with a survey method of sampling. The population in this study were all students of class X, totaling 40 people. The sampling technique used is sampling or part of the population. The data analysis technique used is descriptive statistical analysis. The results showed that interest in volleyball at MA Al Ijtihad Danger was high with a percentage of 78.6%.